EFAS Score — Multilingual development and validation of a patient-reported outcome measure (PROM) by the score committee of the European Foot and Ankle Society (EFAS). Issue 3 (June 2018) - Richter, Martinus; Agren, Per-Henrik; Besse, Jean-Luc; Cöster, Maria; Kofoed, Hakon; Maffulli, Nicola; Rosenbaum, Dieter; Steultjens, Martijn; Alvarez, Fernando; Boszczyk, Andrzej; Buedts, Kris; Guelfi, Marco; et al.
Abstract: Background: A scientifically sound validated foot and ankle specific score validated ab initio for different languages is missing. The aim of a project of the European Foot and Ankle Society (EFAS) was to develop, validate, and publish a new score(the EFAS-Score) for different European languages. Methods: The EFAS Score was developed and validated in three stages: (1) item (question) identification, (2) item reduction and scale exploration, (3) confirmatory analyses and responsiveness. The following score specifications were chosen: scale/subscale (Likert 0–4), questionnaire based, outcome measure, patient related outcome measurement. For stage 3, data were collected pre-operatively and at a minimum follow-up of 3 months and mean follow-up of 6 months. Item reduction, scale exploration, confirmatory analyses and responsiveness were executed using analyses from classical test theory and item response theory. Results: Stage 1 resulted in 31 general and 7 sports related questions. In stage 2, a 6-item general EFAS Score was constructed using English, German, French and Swedish language data. In stage 3, internal consistency of the scale was confirmed in seven languages: the original four languages, plus Dutch, Italian and Polish (Cronbach's Alpha >0.86 in all language versions). Responsiveness was good, with moderate to large effect sizes in all languages, and significant positive association between the EFAS Score and patient-reported improvement. No sound EFAS Sports Score could be constructed. Conclusions: The multi-language EFAS Score was successfully validated in the orthopaedic ankle and foot surgery patient population, including a wide variety of foot and ankle pathologies. All score versions are freely available atwww.efas.co .